Robot-assisted vs. laparoscopic repair of complete upside-down stomach hiatal hernia (the RATHER-study): A prospective comparative single center study. (28th May 2021) - Nocera, F; Wilhelm, A; Schneider, R; Koechlin, L; Daume, D; Fourie, L; Steinemann, D C; von Flüe, M; Peterli, R; Angehrn, F; Bolli, M
Abstract: Objective: Complete upside-down stomach (cUDS) hernias are a subgroup of large hiatal hernias characterized by high risk of life-threatening complications and technically challenging surgical repair including complex mediastinal dissection. In a prospective, comparative clinical study, we evaluated intra- and postoperative outcomes, quality of life and symptomatic recurrence rates in patients with cUDS undergoing robot-assisted, as compared to standard laparoscopic repair (the RATHER-study). Methods: All patients with cUDS herniation requiring elective surgery in our institution between July 2015 and June 2019 were evaluated. Patients undergoing primary open surgery or additional associated procedures were not considered. Primary endpoints were intra- and postoperative complications, 30-day morbidity, and mortality. During the 8-53 months follow-up period, patients were contacted by telephone to assess symptoms associated to recurrence, whereas quality of life was evaluated utilizing the Gastroesophageal Reflux Disease–Health-Related Quality of Life (GERD-HRQL) questionnaire. Results: A total of 55 patients were included. 36 operations were performed with robot-assisted (Rob-G), and 19 with standard laparoscopic (Lap-G) technique. Patients characteristics were similar in both groups. Median operation time was 232 min. (IQR: 145-420) in robot-assisted vs. 163 min. (IQR:112-280) in laparoscopic surgery (p < 0.001). Intraoperative complications occurred in 5/36 (12.5%) cases in the Rob-G group and in 5/19 (26%) cases in the Lap-G group (p = 0.28). No conversion was necessary in either group. Minor postoperative complications occurred in 13/36 (36%) Rob-G patients and 4/19 (21%) Lap-G patients (p = 0.36). Mortality or major complications did not occur in either group. Two asymptomatic recurrences were observed in the Rob-G group only. No patient required revision surgery. Finally, all patients expressed satisfaction for treatment outcome, as indicated by similar GERD-HRQL scores. Conclusion: While robot-assisted surgery provides additional precision, enhanced visualization, and greater feasibility in cUDS hiatal hernia repair, its clinical outcome is at least equal to that obtained by standard laparoscopic surgery.